Enseñanza reflexiva en el aula de lengua extranjera - Martínez Agudo, Juan de Dios (Didáctica. Lengua y Literatura, 2004)
This article highlights the necessity of promoting reflective teaching for the improvement of teaching competence. We must reflect critically on the efficiency of teaching actions in the classroom context. For this reason, we analyse the repercussion of teaching performance on the outcome of foreign language learning.
Keywords: Reflective teaching Teaching performance Language learning